2011
DOI: 10.1007/978-1-4419-7210-1_21
|View full text |Cite
|
Sign up to set email alerts
|

Time-Structure of the Yeast Metabolism In vivo

Abstract: All previous studies on the yeast metabolome have yielded a plethora of information on the components, function and organisation of low molecular mass and macromolecular components involved in the cellular metabolic network. Here we emphasise that an understanding of the global dynamics of the metabolome in vivo requires elucidation of the temporal dynamics of metabolic processes on many time-scales. We illustrate this using the 40 min oscillation in respiratory activity displayed in auto-synchronous continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 67 publications
3
32
0
Order By: Relevance
“…Inhibiting mitochondrial respiration at the level of cytochrome oxidase with hydrogen sulfide (H2S) abated all oscillatory frequencies including the 40 min-period ultradian clock. This result provided proof of principle in support of the idea that multi-scale timekeeping is an emergent property of the overall network involved in metabolism, growth and proliferation of yeast [44,60]. This finding also poses the interesting possibility that, in principle, multi-rhythmic processes could be modulated over the whole frequency range.…”
Section: Prediction Control and Modulation Of Complex Dynamic Behaviorsupporting
confidence: 69%
“…Inhibiting mitochondrial respiration at the level of cytochrome oxidase with hydrogen sulfide (H2S) abated all oscillatory frequencies including the 40 min-period ultradian clock. This result provided proof of principle in support of the idea that multi-scale timekeeping is an emergent property of the overall network involved in metabolism, growth and proliferation of yeast [44,60]. This finding also poses the interesting possibility that, in principle, multi-rhythmic processes could be modulated over the whole frequency range.…”
Section: Prediction Control and Modulation Of Complex Dynamic Behaviorsupporting
confidence: 69%
“…Theoretical simulations indicated that the mitochondrial oscillator's period can be modulated over a wide range of time scales (Cortassa et al, 2004; Aon et al, 2006, 2008b). Although the frequency distribution is broad under normal conditions, the long-term temporal correlations of the mitochondrial network could theoretically allow a change in one time scale to be felt across the frequency range, a feasible behavior in systems exhibiting inverse power law relations (Yates, 1992; West, 1999; Aon et al, 2008c; Sasidharan et al, 2012). These results led to the idea that mitochondrial oscillations may play a role as intracellular timekeeper (Aon et al, 2007a; 2008b,c).…”
Section: Discussionmentioning
confidence: 99%
“…Both NAD(P)H and ATP show maximum production in the reductive phase. Relationships with mitochondrial function, DNA remodeling and duplication, and the cell division cycle in vivo have been further revealed …”
Section: Emergent Self‐organization: a Hallmark Of The Dynamic Behavimentioning
confidence: 99%